Study of Earthquake Activities in the Lokop-Kutacane Fault in Aceh Province, Indonesia - jihad, abdi; Banyunegoro, Vrieslend Haris (Jurnal Fisika dan Aplikasinya, 2021)
The tectonic setting of Aceh is very interesting to be studied. Despite many researches of Aceh’s tectonic setting, still there are many hidden faults waiting to be studied. One of them is Lokop-Kutacane fault which becomes active in 2020. There is an increase in frequency of earthquakes in Lokop-Kutacane fault. Magnitude-fault length analysis indicates that maximum magnitude of Lokop-Kutacane fault is M7,6 but historically it only had M6.8 in the past. CDF and PDF analysis show that the highest probability of earthquake magnitude is between 3 to 4 at 28.9%. Focal mechanism also gives two nodal planes with the direction of strike of 62 and 153. The distribution of earthquakes trend fits the 153 strike nodal plane with the direction of Northwest-Southeast. The calculation of b-value gives 0.78 that indicate that the fault is not able to hold a large amount of stress or the stress will be released in form of small to moderate earthquakes.